COVID-19 rapid evidence profile #23: What is known about anticipated COVID-19 vaccine-delivery program elements, and whether and how federated states are harmonizing these elements across constituent units of federations? - Bhuiya, AR; Wilson, MG; Moat, KA; Gauvin, François-Pierre; Wang, Q; Whitelaw, S; Alam, S; Sharma, K; Ahmad, A; Drakos, A; Dren, N; Bain, T; et al. (My University, 2020)
An overview of the best available research evidence from around the world (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about anticipated COVID-19 vaccine-delivery program elements, and whether and how federated states are harmonizing these elements across constituent units of federations in response to a decision-maker’s request.
Keywords: COVID-19; vaccine-delivery; program; federations; states